2015
DOI: 10.1007/s10571-015-0241-3
|View full text |Cite
|
Sign up to set email alerts
|

Gas1 Knockdown Increases the Neuroprotective Effect of Glial Cell-Derived Neurotrophic Factor Against Glutamate-Induced Cell Injury in Human SH-SY5Y Neuroblastoma Cells

Abstract: Growth arrest-specific 1 (Gas1) protein acts as an inhibitor of cell growth and a mediator of cell death in nervous system during development and is also re-expressed in adult neurons during excitotoxic insult. Due to its structural similarity to the glial cell-derived neurotrophic factor family receptors α (GFRα), Gas1 is likely to interfere with the neuroprotective effect of GDNF. In the present study, we investigated the expression profile of Gas1 during glutamate insults in human SH-SY5Y neuroblastoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We also confirmed the gradual elevation of Gas1 expression in the SH-SY5Y dopaminergic cells that was accompanied by apoptosis in a serum-deprived condition [ 15 ]. Gas1 knockdown increases the protective effect of GDNF against glutamate-induced injury in SH-SY5Y cells [ 23 ], and Gas1 has been reported to be induced and involved in the excitotoxic deaths of hippocampal neurons [ 16 ]. Thus, the data from the present study may also propose a critical question regarding the enrollment of the up-regulation of the Gas1 signal in the mediation of the apoptosis of dopaminergic neurons in the substantia nigra during the pathogenesis of PD.…”
Section: Discussionmentioning
confidence: 99%
“…We also confirmed the gradual elevation of Gas1 expression in the SH-SY5Y dopaminergic cells that was accompanied by apoptosis in a serum-deprived condition [ 15 ]. Gas1 knockdown increases the protective effect of GDNF against glutamate-induced injury in SH-SY5Y cells [ 23 ], and Gas1 has been reported to be induced and involved in the excitotoxic deaths of hippocampal neurons [ 16 ]. Thus, the data from the present study may also propose a critical question regarding the enrollment of the up-regulation of the Gas1 signal in the mediation of the apoptosis of dopaminergic neurons in the substantia nigra during the pathogenesis of PD.…”
Section: Discussionmentioning
confidence: 99%
“…GAS-1 and VEGF-B were increased, and CXCL16 was reduced compared to sham levels. Of these three proteins GAS-1 and CXCL16 may be the best options for drug target validation, both proteins are known to modulate neuronal cell death involving glutamate excitotoxicity, a common feature of brain injuries ( Globus et al, 1995 ; Mellström et al, 2002 ; Rosito et al, 2012 ; Rosito et al, 2014 ; Sun et al, 2016 ; Wang et al, 2016a ; Zarco et al, 2012 ) and as such may make them ideal candidate drug targets for evaluation. While there are no direct reports of the actions of VEGF-B on the traumatized brain, it is tempting to speculate that the homeostatic and pro-neurogenesis properties of the protein would be ripe for exploration in TBI ( Nag et al, 2002 ; Sun et al, 2004 ; Sun et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…In hippocampal neurons, Gas1 induces cell death after excitotoxic insults, inhibiting the signaling induced by GDNF. [99,100] Nevertheless, during cerebellar development Gas1 induces the proliferation of cerebellar granule neuron progenitors in a Shh-dependent manner. [71,96] …”
Section: Gas1 Protein Structure and Expressionmentioning
confidence: 99%
“…This leads to the translocation of BAD to the mitochondria and the release of cytochrome-C to the cytosol which in turn induces the activation of Caspases 9 and 3. [107,108,[115][116][117][118] Recently Wang and et al [100] demonstrated that Gas1 promotes excitotoxicity in dopaminergic neurons by inhibiting the GDNF signaling pathway.…”
Section: Gas1 Inhibits the Signaling Induced By Gdnf And Arteminmentioning
confidence: 99%